MENUMBUHKAN KESADARAN DALAM MANAJEMEN DAN STRATEGI PENGEMBANGAN INDUSTRI KREATIF PADA SEKTOR USAHA KECIL MENENGAH (UKM) - Wartomo Wartomo (JGK (Jurnal Guru Kita), 2022)
Raising Awareness in the Management and Development Strategy of the Creative Industries in the Small and Medium Enterprises (SMEs) Sector. Management and economic development strategies in the creative industry sector and Small and Medium Enterprises (SMEs) are often stated as a safety valve for the national economy, but until now the development of SMEs is still faced with various problems, especially those originating from an unconducive business climate as a result of the tendency to develop free competition. Efforts to solve these problems cannot be entirely left to the Government because there are things that must be resolved by SMEs themselves. Government policies implemented in various forms of programs only act as stimulants. The creative industry and SMEs themselves actually have various potential advantages, including the number and characteristics of SMEs. From the potential of the creative industry, SMEs should be able to develop management and strategies to deal with an unconducive business climate, or adapt themselves to these conditions. Various solutions can be made in the creative industries by SMEs, including by developing cooperation in cooperatives, building business centers and clusters to building business partnerships. In supporting these efforts, the government can play a role both as a regulator that is able to reduce the impact of free competition and/or as a facilitator that can strengthen internal conditions in the creative industries and SMEs. in free competition.